2021
DOI: 10.1001/jamapsychiatry.2021.1813
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Attempts of Muslims Compared With Other Religious Groups in the US

Abstract: Suicide is one of the leading causes of death and has steadily increased throughout the past 2 decades. 1 Religious affiliation may be associated with a lower risk for both suicide attempt and death through multiple mechanisms, including the promotion of social support, personal empowerment, healthy lifestyle, and commitment to religious life-preserving morals. 2 In the US, Muslim individuals represent a religious minority group who are vulnerable to religious discrimination but may access mental health servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 4 publications
(4 reference statements)
0
18
0
Order By: Relevance
“…Muslim groups in the U.S. represent a religious minority vulnerable to discrimination that may exacerbate pre- and post-migration-related stressors (Alemi & Stempel, 2018 ). This has significant implications for second-generation refugees and immigrants that identify as Muslim in the U.S. A recent study examining suicide attempts of Muslims compared to other religious groups in the US found that Muslims were 2.18 (95% CI 1.13–4.20; P < .05) times more likely to report a lifetime suicide attempt compared with Protestants (Awaad et al, 2021 ). This supports prior calls by leading migrant experts worldwide to address discrimination at the health system level as a priority in policy development (Pottie et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Muslim groups in the U.S. represent a religious minority vulnerable to discrimination that may exacerbate pre- and post-migration-related stressors (Alemi & Stempel, 2018 ). This has significant implications for second-generation refugees and immigrants that identify as Muslim in the U.S. A recent study examining suicide attempts of Muslims compared to other religious groups in the US found that Muslims were 2.18 (95% CI 1.13–4.20; P < .05) times more likely to report a lifetime suicide attempt compared with Protestants (Awaad et al, 2021 ). This supports prior calls by leading migrant experts worldwide to address discrimination at the health system level as a priority in policy development (Pottie et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Spiritual bypass is a phenomenon that occurs when individuals focus on R/S coping to avoid engagement with their inner psychological experiences (Welwood, 1984), ultimately bypassing professional and other forms of help-seeking and self-work (Fox et al, 2020). Spiritual bypass may be particularly relevant for Muslims living in the United States (MLUS), who avoid psychological help despite facing a mental health crisis, evidenced by increasing levels of discrimination (Federal Bureau of Investigation [FBI], 2020), poorer mental health relative to their non-Muslim counterparts (Amer & Hovey, 2012; Awaad et al, 2021), and being twice as likely as those of other faith groups to report past suicide attempts (Awaad et al, 2021). There is a crucial need to examine the effects of spiritual bypass in MLUS.…”
Section: Religious and Spiritual (R/s) Coping In Muslimsmentioning
confidence: 99%
“…Discussion MLUS face increased rates of discrimination (Samari et al, 2018), depression (Amer & Hovey, 2012), and suicide (Awaad et al, 2021), yet are less likely to seek mental health care (Aloud & Rathur, 2009;Khan, 2006). Some (e.g., Khan et al, 2019) have suggested that Islamophobia is impacting MLUS' attitudes toward seeking and using formal mental health services, and that therapy needs to be better catered to MLUS needs.…”
Section: Aimmentioning
confidence: 99%
“…Relatedly, some studies suggest that MLUS experience poorer mental health relative to their non-Muslim counterparts. For example, Arab MLUS have shown higher rates of depression and anxiety compared to other minority groups (Amer & Hovey, 2012), and MLUS also reported higher rates of suicide attempts compared to those of other faith groups, as well as atheists and agnostics (Awaad et al, 2021).…”
Section: Double Stigma and Islamophobiamentioning
confidence: 99%